Inlet turbulence generation for Large Eddy Simulation: applications to fluid-structure interaction problems - Castro, Hugo Guillermo (2014)
Fil: Castro, Hugo Guillermo. Universidad Nacional del Litoral. Facultad de Ingeniería y Ciencias Hídricas; Argentina.